Evaluation of litter type and dietary coarse ground corn inclusion on broiler live performance, gastrointestinal tract development, and litter characteristics. (13th February 2015) - Xu, Y.; Stark, C. R.; Ferket, P. R.; Williams, C. M.; Nusairat, B.; Brake, J.
Abstract : Two 49 d floor pen studies were conducted to evaluate the effects of litter type and dietary coarse ground corn (CC) inclusion on broiler live performance, gastrointestinal tract (GIT) development, and litter characteristics. Experiment 1 was a 2 × 2 factorial arrangement of 2 genders (male or female) and 2 CC levels (0 or 50%). From 15 to 35 d, the addition of CC decreased feed intake ( P < 0.01) and BW gain ( P  < 0.05) of males but not females. The inclusion of CC decreased feed intake ( P < 0.01) and BW gain ( P < 0.01) from 0 to 49 d but improved adjusted feed conversion ratio (AdjFCR) from 35 to 49 d ( P  < 0.05). Male broilers exhibited better live performance than females during the study as evidenced by greater feed intake ( P < 0.01) and BW gain ( P < 0.01), and improved FCR ( P < 0.01), but with increased mortality ( P  < 0.05). The inclusion of CC increased relative gizzard weight ( P < 0.01) and decreased relative proventriculus weight ( P < 0.01) at 49 d. Experiment 2 was a 2 × 2 factorial arrangement of 2 CC levels (0 or 50%) and 2 litter types (ground old litter or new wood shavings litter). The inclusion of CC decreased feed intake throughout the experiment without affecting final BW when only males were used and improved FCR after 25 d ( P < 0.01). New litter improved FCR from 1 to 14 d ( P < 0.01). At 49 d, the birds fed the CC diet had reduced excreta nitrogen ( P  < 0.05) and litter moisture ( P  < 0.05). In conclusion, 50% CC inclusion initially produced negative effects on live performance that became positive as BW increased. The effects of CC became evident at an earlier age for males. New litter had only a marginal benefit on broiler live performance.